Pengunaan Media Pembelajaran Scratch pada SMP - Hafif Assulamy; Aunnurahman Aunnurahman; Halida Halida (Journal on Education, 2023)
This research is a literature review that explores the use of Scratch learning media in the context of computer systems learning. The literature review method is used to combine and analyze research results that have been previously published in national journals. Scratch, as a visual programming platform, has played an important role in supporting programming learning and understanding of computer concepts at various levels of education. In this research, researchers collected references from previous studies that are relevant to this topic. With a descriptive approach, this research explains and analyzes the development of Scratch use in various forms, including online Scratch projects and Android-based applications. The research results show that Scratch has facilitated more interactive, in-depth, and creative learning for students, increased interest in programming, and expanded inclusive learning opportunities across a variety of subjects. These studies reveal a wide variety in the use of Scratch, from evaluations of its effectiveness to its impact on students' concept understanding and creativity, reinforcing Scratch's role as an educational tool that supports problem solving and concept mastery. In an ever-evolving educational context, Scratch shows exciting and varied potential, leading to a more dynamic and inclusive educational future.